Value of Doppler ultrasound in the management of infantile hemangioma. - Jebbouje, S.; Hali, F.; Moubine, I.; Chebani, W.; Chiheb, S. (European Journal of Pediatric Dermatology, 2025)
Oral propranolol (Pr) is the standard treatment for infantile hemangioma (IH), the most common vascular tumor of childhood. Therapy must be continued until the end of the proliferative phase, whose clinical assessment can be challenging, particularly in subcutaneous forms. Doppler ultrasound (DUS) is a valuable tool that can guide clinicians in making appropriate therapeutic decisions. In this retrospective, observational, single-center study, we enrolled all children with IH treated with Pr for 6-12 months who also underwent DUS. We evaluated the contribution of DUS in guiding the decision to discontinue Pr at the end of the proliferative phase or to restart treatment in the event of suspected recurrence. A total of 332 children were included, of whom 220 underwent DUS after 6 months of Pr. Among these, 182 showed reduced vascular activity, suggesting discontinuation of propranolol, while 38 had persistent vascular activity, warranting continuation of therapy. After a median follow-up of 36 months, the clinical findings indicated regression in all cases, while Doppler ultrasound confirmed regression in 108/220 cases, but indicated recurrence in 112/220 cases, thus leading to the resumption of propranolol treatment. Recurrent IHs were characterized by mixed or deep forms, with very low vascular activity. After another 18 months, the 112 patients who had resumed propranolol underwent another DUS: in 75 cases, the DUS did not reveal VA, which was still present in 37 cases; in these latter cases, too, PR was not resumed, as the clinical judgment indicating regression of IH prevailed. To our knowledge, there are only two small-series studies on the use of DUS in IH treated with propranolol, one of which did not evaluate distant recurrence. In our study, Doppler ultrasound proved useful in conjunction with clinical examination in the therapeutic management of infantile hemangiomas.